Strategi Digitalisasi dan Konten Lokal Budaya Bangka untuk Daya Saing UMKM Otak-Otak - Achmad Riyadi; Hattami Amar (Pusat Riset dan Inovasi Nasional, 2026)
Otak-otak MSMEs in Bangka Belitung play an important role in local economic development and culinary heritage preservation, yet face challenges in utilizing social media and integrating local cultural values into digital marketing. This study aims to formulate digitalization and marketing strategies based on Bangka cultural content to enhance MSME competitiveness. Using a mixed-methods explanatory sequential design, data were collected from seven MSME owners through questionnaires and in-depth interviews. Results show strong internal resources (RBV) with an average score of 4.63, while Local Content Marketing scored lower at 3.11. The findings highlight the need for cultural branding, digital capacity building, and multi-stakeholder collaboration.